2017
DOI: 10.1634/theoncologist.2016-0414
|View full text |Cite
|
Sign up to set email alerts
|

A Predictive Score for Thrombosis Associated with Breast, Colorectal, Lung, or Ovarian Cancer: The Prospective COMPASS–Cancer-Associated Thrombosis Study

Abstract: The COMPASS‐CAT study was undertaken in outpatients with breast, colon, lung, or ovarian cancer. The aim of the study was to identify the most relevat risk factors for symptomatic thromboembolism and to develop a risk assessment model applicable to patients after the initiation of anticancer treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
186
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 197 publications
(194 citation statements)
references
References 39 publications
3
186
0
5
Order By: Relevance
“…These are hospitalization within the last 3 months prior to assessment, presence of cardiovascular risk factors and/or cardiovascular comorbidities, overweight or obesity, personal history of thrombosis, and a time since cancer diagnosis less than 6 months from the assessment. The clinical predictors of VTE identified in the ROADMAP‐CAT study are the same as those identified in a large prospective study performed in outpatients with solid tumors, including lung cancer, which resulted in the derivation of the COMPASS‐CAT RAM .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These are hospitalization within the last 3 months prior to assessment, presence of cardiovascular risk factors and/or cardiovascular comorbidities, overweight or obesity, personal history of thrombosis, and a time since cancer diagnosis less than 6 months from the assessment. The clinical predictors of VTE identified in the ROADMAP‐CAT study are the same as those identified in a large prospective study performed in outpatients with solid tumors, including lung cancer, which resulted in the derivation of the COMPASS‐CAT RAM .…”
Section: Discussionmentioning
confidence: 99%
“…Calibration of the models was controlled with the Hosmer-Lemeshow test. At the last part of the study, the COMPASS-CAT RAM (described elsewhere [18]) was applied and the effect of the incorporation of the clinically relevant biomarkers was analyzed. Model discrimination performance was evaluated by calculating sensitivity, specificity, positive predictive value, and negative predictive value for both cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…Khorana score was the first validated risk assessment model (RAM) for identifying VTE high-risk patients receiving chemotherapy. After this publication, different RAM have been published and some of them have been validated (Table 3) [24][25][26][27][28][29][30][31][32]. Other RAM addressed to specific tumors such as THROLY [33] or testicular germ cell tumors [34].…”
Section: Prophylaxis Of Vte In Ambulatory Cancer Patients During Systmentioning
confidence: 99%
“…It is recommended to use a validated RAM to assess VTE risk (level of evidence: grade 2C). Vienna CATS score [25] PROTECHT score [26] CONKO score [27] Oncothromb-Tic Onco score extended [28,29] Compass-CAT score [30]…”
Section: Recommendationsmentioning
confidence: 99%
“…1,2 Due to the heterogeneity of cancer and the various risks of VTE development including different biomarkers, 3 currently no routine prophylaxis is recommended in any guidelines for outpatients with cancer receiving chemotherapy with a few exceptions. [4][5][6][7] At present, several VTEassessment models for chemotherapy-associated thrombosis exist, which are intended to help in the identification of patients at a higher risk of VTE [8][9][10][11][12] and who may possibly benefit from thromboprophylaxis. Due to poor discriminatory performance, most of the recently established VTE-assessment models have proven to be of limited clinical utility because of the low predictive value of VTE events in subsequent studies, particularly in studies based on a single cancer cohort.…”
Section: Introductionmentioning
confidence: 99%